Photodegradation and photostabilization of historic silks in the museum environment – evaluation of a new conservation treatment. - Tatiana Koussoulou (Papers from the Institute of Archaeology, 1999)
This paper explains the mechanisms of deterioration of the silk fibres and dyes used to make historic textiles displayed in museums, and introduces a new method of protection of historic silks by the application of materials known as light stabilizers directly to the objects. Testing of the suitability of these stabilizers, using silk fabrics dyed with traditional natural dyestuffs resembling the original historic objects, is also described.
Keywords: conservation; museum; photostabilization; photodegradation; historic silk; Silk